Gender disparity in the associations of overweight/obesity with occupational activity, transport to/from work, leisure-time physical activity, and leisure-time spent sitting in working adults: A cross-sectional study - Xu, Chun-Xiao (J Epidemiol, 2017)
BACKGROUND: The associations of occupational activity (OA), commuting, leisure-time physical activity (LTPA), and sitting with overweight/obesity in working adults are controversial. This study explored these factors with the risk of overall and abdominal overweight/obesity in a Chinese working population and whether these associations differ by gender. METHODS: A cross-sectional study was conducted. Data analysis was done among 6739 employed participants. Multivariate logistic regression was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for the studied associations. RESULTS: For male employees, those with heavy OA had a lower overall (OR 0.76; 95% CI, 0.62–0.93) and abdominal (OR 0.76; 95% CI, 0.62–0.93) overweight/obesity risk than those with light OA. Those with LTPA ≥150 min/week had a lower risk of overall (OR 0.73; 95% CI, 0.56–0.96) and abdominal (OR 0.70; 95% CI, 0.53–0.91) overweight/obesity than those with LTPA <150 min/week. Men with leisure-sitting time <2.5 h/day had a significantly lower risk of abdominal overweight/obesity than those sitting ≥4 h/day (OR 0.80; 95% CI, 0.65–0.99). And men who cycled to/from work had a lower risk of overall (OR 0.69; 95% CI, 0.53–0.90) and abdominal overweight/obesity (OR 0.71; 95% CI, 0.54–0.92) than passive transports. However, the above significant associations disappeared among female employees. CONCLUSIONS: Heavy OA, cycling to/from work, and LTPA were associated with lower risk of overall or abdominal overweight/obesity in male employees. Reducing leisure sitting time can also help male employees reduce the risk of abdominal overweight/obesity. More research on gender disparity in the risk of overweight and obesity should be done.